Optimizing Income Tax Article 21: Simultaneous Use of Gross and Gross Up Methods (Case Study of PT. X) - Sulastri, Ulfa; Nisa, Farhatun (International Journal of Pertapsi, 2025)
This study aims to analyze the effectiveness of the application of mixed method (gross and gross-up) in the calculation of Income Tax Article 21. The analysis focuses on the suitability of the method with the applicable tax provisions, as well as its impact on tax liabilities, fiscal efficiency, and cash flow management of the company. This research uses a descriptive qualitative approach with a case study method at PT X. The data used are primary and secondary data collected through observation, interviews, and documentation on the calculation of Income Tax 21 for the December period for the Director position. The results showed that the application of mixed method is a tax planning strategy that is legally valid, adaptive to the company's financial condition, and able to increase the efficiency of the tax burden, especially in the face of irregular income. In its application, this method faces challenges in the form of technical complexity of calculations and limitations of the tax administration system. Therefore, it is necessary to prepare systematic and accountable documentation, as well as active communication with tax authorities to mitigate the risk of fiscal correction and ensure the suitability of the withholding method with the company's financial condition.